Risk Management Analysis and Mitigation of Problematic Financing in Murabahah Contract (Case Study at KSPPS BMT Arta Buana Metro, Tulang Bawang Branch). - Maratus Sholikah; M afifuddin (Universitas Islam Darul 'ulum Lamongan, 2026)
This study aims to analyze the implementation of risk management and mitigation strategies for problematic financing in murabahah contracts at KSPPS BMT Arta Buana Metro, Tulang Bawang Branch, as well as to identify the causal factors. This research uses a qualitative method with a phenomenological approach. Data were collected through observation, in-depth interviews with the branch head and staff, and documentation. The data analysis technique uses the Miles and Huberman model. The results indicate that the implementation of risk management at BMT Arta Buana is carried out through the stages of identification, measurement, control, and monitoring by consistently applying the 5C principle (Character, Capacity, Capital, Collateral, Condition) from the survey stage to post-realization. The mitigation strategies implemented include preventive measures (strict 5C analysis), curative measures (persuasive and familial approaches, intensive communication), and financing restructuring (rescheduling) for members who meet the criteria. The main factors causing problematic financing are internal factors (weak analysis/monitoring) and external factors, dominantly due to business failure and declining member economy.